2011
DOI: 10.1242/jeb.061945
|View full text |Cite
|
Sign up to set email alerts
|

From population-level effects to individual response: modelling temperature dependence in Gammarus pulex

Abstract: SUMMARYPopulation-level effects of global warming result from concurrent direct and indirect processes. They are typically described by physiologically structured population models (PSPMs). Therefore, inverse modelling offers a tool to identify parameters of individual physiological processes through population-level data analysis, e.g. the temperature dependence of growth from size-frequency data of a field population. Here, we make use of experiments under laboratory conditions, in mesocosms and field monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In parallel to its effect on parasite traits, temperature also affected certain traits of the hosts. First, the survival of gammarids was decreased at high temperature, as already shown in other studies 55,56 , while infection with parasites also led to a higher mortality of gammarids. However, the influence of parasites on host survival was not affected by temperature.…”
Section: Groupsupporting
confidence: 72%
See 1 more Smart Citation
“…In parallel to its effect on parasite traits, temperature also affected certain traits of the hosts. First, the survival of gammarids was decreased at high temperature, as already shown in other studies 55,56 , while infection with parasites also led to a higher mortality of gammarids. However, the influence of parasites on host survival was not affected by temperature.…”
Section: Groupsupporting
confidence: 72%
“…As for other ectotherm species 52 , temperature has been shown to affect amphipods in several ways, influencing for instance their metabolism 53 55 , growth 56 , or activity 54 . Similarly, most parasites are also affected by temperature in diverse ways 57 .…”
Section: Introductionmentioning
confidence: 99%
“…Variation in the seasonal distribution of acanthocephalan parasites also suggests that their prevalence could be linked to climatic conditions (VanCleave, 1916;Muzzall & Rabalais, 1975;Brown, 1989). In parallel, some effects of temperature on gammarid traits, such as their immune system (Le Moullac & Haffner, 2000), their growth (Moenickes et al, 2011), their locomotor activity (Issartel et al, 2005) or their metabolism (Roux & Roux, 1967;Issartel et al, 2005;Foucreau et al, 2014), are also likely to modify the interaction between gammarids and their parasites, such as the prevalence or the probability of encounters. For instance, Guinnee & Moore (2004) found that the effect of an acanthocephalan parasite on its insect host depended on temperature: Infection negatively impacted host fecundity only at the highest temperature tested.…”
Section: Introductionmentioning
confidence: 99%
“…Background mortality was assumed to be independent of temperature (Moenickes et al, 2011). Once a day, background mortality is applied via a constant probability of dying due to, for example, predation, cannibalism, or age.…”
Section: Population Modelmentioning
confidence: 99%
“…Once a day, background mortality is applied via a constant probability of dying due to, for example, predation, cannibalism, or age. Background mortality was assumed to be independent of temperature (Moenickes et al, 2011). For computational reasons, population sizes were kept at a certain level which sometimes resulted in extinctions due to the stochastic nature of background mortality implementation.…”
Section: Population Modelmentioning
confidence: 99%